Nutrients Bioaccessibility and Anti-inflammatory Features of Fermented Bee Pollen: A Comprehensive Investigation - Filannino, Pasquale; Di Cagno, Raffaella; Vincentini, Olimpia; Pinto, Daniela; Polo, Andrea; Maialetti, Francesca; Porrelli, Annalisa; Gobbetti, Marco (Frontiers in Microbiology, 2021)
We compared raw bee-collected pollen (Raw-BCP), spontaneously fermented BCP (Unstarted-BCP) and BCP fermented with selected microbial starters (Started-BCP) to deepen whether fermentation may favourably affect the nutrients bioaccessibility and functional features of BCP. Under in vitro gastrointestinal batches, the highest serum-availability of phenolic compounds was found in Started-BCP, highlighting the positive effect exerted by selected microbial starters. The same effect was not found in spontaneously fermented BCP. In Caco-2 cells stressed by a pro-inflammatory stimulus, the treatment with Started-BCP halted the increase of pro-inflammatory mediators level. Started-BCP counteracted efficiently the deleterious effects of inflammatory stimuli on the integrity of the Caco-2 cells monolayer and its barrier function. Started-BCP successfully counteracted the H2O2-induced intracellular accumulation of ROS in Caco-2 cells. A protective role against LPS-induced inflammation was exerted by Started-BCP in human keratinocytes. The same protective effects on Caco-2 and keratinocyte cell lines were negligible after treatments with Raw- or Unstarted-BCP.